1995
DOI: 10.1002/pola.1995.080331014
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion polymerization of butyl acrylate. IV. Effect of emulsifier concentration

Abstract: The oil/water microemulsion polymerizations of butyl acrylate initiated by a water (ammonium peroxodisulfate, APS) or oil (dibenzoyl peroxide, DBP) soluble radical initiator at different emulsifier concentrations were investigated. The rate of polymerization vs. conversion curve shows two intervals. The rate of polymerization is found to decrease with the emulsifier concentration. This finding was discussed in terms of the decrease of both radical and monomer concentration, the chain transfer to emulsifier, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…When one considers the hydrophobic nature of St, the migration of monomeric radicals into the aqueous phase is not favored. This step could be facilitated by a chaintransfer reaction from the primary radical to an emulsifier molecule, 21,22 which may diffuse into the aqueous phase very easily through the fast dynamic exchange of emulsifier molecules between the oil/water interface and the aqueous phase. The monomer conversion achieved by the thermally initiated polymerization is about two orders of magnitude lower than that achieved by the peroxodisulfate-initiated polymerization.…”
Section: Role Of Thermal Polymerizationmentioning
confidence: 99%
“…When one considers the hydrophobic nature of St, the migration of monomeric radicals into the aqueous phase is not favored. This step could be facilitated by a chaintransfer reaction from the primary radical to an emulsifier molecule, 21,22 which may diffuse into the aqueous phase very easily through the fast dynamic exchange of emulsifier molecules between the oil/water interface and the aqueous phase. The monomer conversion achieved by the thermally initiated polymerization is about two orders of magnitude lower than that achieved by the peroxodisulfate-initiated polymerization.…”
Section: Role Of Thermal Polymerizationmentioning
confidence: 99%
“…The main location of NMA at the interfacial layer decreases the monomer concentration at the reaction loci (dilution effect) 22 and the rate of polymerization as well. The largest Rp,max, 2 or smallest R 112 for MMA results from increased agglomeration of particles which first decreases Rp,max,l (due to increased deactivation of reaction loci) and later increases Rp.max, 2 (due to accumulation of radicals in the large particles).…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…We have earlier reported that n n lies well below 0.5 for the small PBuA particles with diameter around and below 50 nm. 40,41 In the present paper n n is ca. 0.9 for the weight ratio BuA/SDS (9.0/ 20) = 0.45.…”
Section: Resultsmentioning
confidence: 99%